Czech Republic : Enhancing the Prospects for Growth with Fiscal Stability - World Bank (Washington, DC, 2013)
This public expenditure review analyzes recent developments in the Czech Republic, and future prospects for growth, with fiscal stability. In analyzing the strategic setting, where a central thrust of this strategy is the accession to the European Union (EU), the report suggests than an appropriate medium-term target for fiscal policy, would be to bring down the overall deficit of the government to one-two percent of GDP, as an intermediate step towards the EU's stability/growth path objectives, emphasizing that much of the adjustment should come from the expenditure side. Given the main purpose of the report - to take this expenditure adjustment challenge as a mean to achieve potential efficiency gains, while limiting attending costs - a reform policy should pursue an ongoing process of review, revision, and re-definition of the role of government intervention. Indeed, to succeed, the process of expenditure reform needs to be firmly grounded in the development of analytic capacities, linked with institutional, and procedural enhancement for fiscal management. The report explores the expenditure reform opportunities, and cost of bank restructuring, focusing on relieving The Konsolidacni Banka (KoB) from its status as a bank, on streamlining recoveries, and asset disposal methods, and on improving the legal framework for debt resolution. It reviews the state pension program, suggesting limited indexation to the consumer price index, elimination of the actuarially unfair aspects of early retirement provisions, to increase statutory retirement, while extending the minimum contribution period for full pension. To strengthen fiscal management, it is proposed that the medium-term outlook be expanded into a full-fledged medium-term fiscal framework, extra-budgetary funds be consolidated, and, activity/service-based articulation of the state budget be initiated.